2016
DOI: 10.1002/cbic.201500676
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐Tuning Covalent Inhibition of Bacterial Quorum Sensing

Abstract: Emerging antibiotic resistance among human pathogens has galvanized efforts to find alternative routes to combat bacterial virulence. One new approach entails interfering with the ability of bacteria to coordinate population-wide gene expression, or quorum sensing (QS), thus inhibiting the production of virulence factors and biofilm formation. We have recently developed such a strategy by targeting LasR, the master regulator of QS in the opportunistic human pathogen Pseudomonas aeruginosa, through the rational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
0
27
0
1
Order By: Relevance
“…aeruginosa. [40] These compounds and especially a b-fluorinated derivative ICT-F (6)c ovalently blocked the LasR receptor at Cys79 and inhibited swarming motilityb y4 4% at 150 mm and by 34 %a t2 0mm and also reducedp yocyanin production( Figure 3a). In contrast, the bro-minatedI TC-Br (7)d id not bind covalently and was aL asR agonist that increased swarming motilityu pt o2 .5-fold at 20 mm of ITC-Br in P. aeruginosa PA14.…”
Section: Blockingahl Receptorsmentioning
confidence: 95%
See 2 more Smart Citations
“…aeruginosa. [40] These compounds and especially a b-fluorinated derivative ICT-F (6)c ovalently blocked the LasR receptor at Cys79 and inhibited swarming motilityb y4 4% at 150 mm and by 34 %a t2 0mm and also reducedp yocyanin production( Figure 3a). In contrast, the bro-minatedI TC-Br (7)d id not bind covalently and was aL asR agonist that increased swarming motilityu pt o2 .5-fold at 20 mm of ITC-Br in P. aeruginosa PA14.…”
Section: Blockingahl Receptorsmentioning
confidence: 95%
“…The production of the swarming surfactant rhamnolipid which Pseudomonas requires to lower surface tension is RhlR regulated by transcription of the rhl genes. The Meijler group developed synthetic AHLs with an isothiocyanate (ITC) warhead mimicking 3‐oxo‐C12‐HSL of P. aeruginosa . These compounds and especially a β‐fluorinated derivative ICT‐F ( 6 ) covalently blocked the LasR receptor at Cys79 and inhibited swarming motility by 44 % at 150 μ m and by 34 % at 20 μ m and also reduced pyocyanin production (Figure a).…”
Section: Swarming and Bacterial Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] A subsequent study by the same group reported several series of new inhibitors, one of which, fluoro-substituted ITC-12, displayed complete covalent modification of LasR, as well as promising in vivo results. [31] Covalent inhibitor of MEP: The methylerythritol phosphate (MEP) pathway is an essential metabolic pathway found in protozoa, including malaria parasites, and bacteria but absent in higher eukaryotes, making it a highly attractive target for the discovery of novel anti-infective agents. Notably, IspD, the third catalytic enzyme of the MEP pathway of different malaria parasites, has a cysteine in the vicinity of the catalytic site.…”
Section: Covalent Inhibitors Extending Beyond a Given Enzyme Class: Tmentioning
confidence: 99%
“…The Meijler group studies QS in bacterial pathogens using a range of elegant chemical approaches. Michael Meijler first outlined the origins of his novel electrophilic probes that are designed to bind LuxR-type QS receptors covalently, leading to inhibition of QS-regulated gene expression (26,27). His lab has applied these probes, along with newer photoactivatable probes, as molecular tools to obtain new insights into the mechanisms of QS.…”
Section: How? Design Principles For Signals Network and Inhibitorsmentioning
confidence: 99%